Expression and functionality of TRPV1 in breast cancer cells - Weber LV (Dove Medical Press, 2016)
Lea V Weber,1 Klaudia Al-Refae,1 Gerhard Wölk,2 Gabriele Bonatz,3 Janine Altmüller,4 Christian Becker,4 Günter Gisselmann,1 Hanns Hatt1 1Department of Cell Physiology, Ruhr‑University Bochum, Bochum, 2Herz-Jesu-Krankenhaus, Dernbach, 3Augusta Kliniken Bochum, Bochum, 4Cologne Center for Genomics, University of Cologne, Cologne, Germany Abstract: Transient receptor potential (TRP) channels contribute to the regulation of intracellular calcium, which can promote cancer hallmarks in cases of dysregulation of gene transcription and calcium-dependent pro-proliferative or anti-apoptotic mechanisms. Several studies have begun to elucidate the roles of TRPV1, TRPV6, TRPM8, and TRPC1 in cancer progression; however, no study has examined the expression profiles of human TRP channels in breast cancer on a large scale. This study focused on the expression and functionality of TRPV1, a nonselective cation channel that was found to be expressed in different carcinoma tissues. Next-generation sequencing analyses revealed the expression of TRPV1 in several native breast cancer tissues, which was subsequently validated via reverse transcriptase-polymerase chain reaction. Activation of TRPV1 by its ligand capsaicin was associated with the growth inhibition of some cancer cell types; however, the signaling components involved are complex. In this study, stimulation by the TRPV1 agonist, capsaicin, of SUM149PT cells, a model system for the most aggressive breast cancer subtype, triple-negative breast cancer, led to intracellular calcium signals that were diminished by the specific TRPV1 antagonist, capsazepin. Activation of TRPV1 by capsaicin caused significant inhibition of cancer cell growth and induced apoptosis and necrosis. In conclusion, the current study revealed the expression profiles of human TRP channels in 60 different breast cancer tissues and cell lines and furthermore validated the antitumor activity of TRPV1 against SUM149PT breast cancer cells, indicating that activation of TRPV1 could be used as a therapeutic target, even in the most aggressive breast cancer types. Keywords: TRP channels, TRPV1, next-generation sequencing, breast cancer, apoptosis, necrosis, anti-proliferative